Problems and solutions for seabird bycatch in trawl fisheries. (December 2014) - Wanless, R. M.; Maree, B. A.
<x xml:space="preserve">Abstract</x> Read the Feature Paper: Significant reductions in mortality of threatened seabirds in a South African trawl fishery and the Commentaries on this Feature Paper: Minimizing seabird by‐catch in industrial fisheries; Challenges in seabird by‐catch mitigation